An evaluation of the impact of e-verification on counterfeit agricultural inputs and technology adoption in Uganda - Ashour, Maha; Billings, Lucy; Gilligan, Daniel O.; Karachiwalla, Naureen (International Food Policy Research Institute, 2015)
In Uganda, use of high-quality agricultural inputs like hybrid seed, agrochemicals, and fertilizer is extremely low. This depresses farm incomes and contributes to low agricultural productivity that continues to be hampered by poor agronomic practices, low quality germplasm, declining soil fertility, and losses due to pests, disease, and postharvest handling practices. Low levels of agricultural technology adoption have been compounded by a lack of farmer trust in the current inputs supply system, which has been plagued by counterfeiting. Counterfeit products range from benign fake or adulterated materials to banned substances that are harmful to crops and human health. Counterfeit agricultural inputs directly reduce productivity and, together with the perception of widespread counterfeiting, reduce demand for high-quality inputs. This lowers input prices and reduces profits for producers of genuine products, causing a form of “adverse selection” in which counterfeit products push high-quality genuine products out of the market.